(untitled) (Journal of the Pakistan Medical Association, 2021)
Although body fluid adenosine deaminase (ADA) level is useful for diagnosing tuberculosis but little is known about joint fluid ADA level in tuberculous (TB) arthritis. This study aimed to evaluate the diagnostic value of synovial fluid ADA (SF-ADA) in TB arthritis. Of 43 patients enrolled, nine had confirmed TB arthritis. Fourteen had non-TB septic arthritis, and 20 patients had non-infectious etiologies. The SF-ADA levels were significantly elevated in patients with TB arthritis compared to those with non-infectious origin (P <0.05). All SF-ADA levels were ?76 U/L in TB arthritis and ? 60 U/L in non-infectious synovial fluid. The ADA was not different between TB arthritis and non-TB septic arthritis (P = 0.87). The possibility of identifying synovial fluid with an ADA under 60-76 U/L of tuberculous etiology may be very low. In addition, an SF-ADA ?76 U/L with negative ordinary bacterial culture results is highly suspicious for TB arthritis. Continuous...